LETROZOLE WITH OR WITHOUT GONADOTROPIN AS A FIRST-LINE OVULATION INDUCTION IN ANOVULATORY INFERTILE WOMEN DUE TO POLYCYSTIC OVARY SYNDROME - Alizzi, Fadia J (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objective is to evaluate the clinical outcome of using letrozole alone or with gonadotropin as first-line ovulation induction in anovulatory infertile polycystic ovary women. Methods: A prospective single-arm study. 80 infertile polycystic ovarian syndrome (PCOS) women had been recruited between January and October 2017. Letrozole on day 2â€“3 of the cycle was given. The women are sorted into two groups according to the size of the dominant follicle on day 7 or 8, Group A (letrozole only group) and Group B (letrozole plus gonadotropin). Results: In our study, the overall pregnancy rate was (67.5%) and ovulation rate was 91.3%. The ovulation rate was significantly higher in Subgroup A than B (97.9% vs. 81.3%). Pregnancy rate was higher in Subgroup A (72.9% vs. 59.4%), but it was statistically not significant. The number of follicles was significantly higher in Subgroup B. Endometrial thickness, miscarriages, ovarian hyperstimulation syndrome, and multiple pregnancies were not statistically significant. Lower cycle number independently and significantly predict clinical pregnancy, while body mass index has a modest effect. Conclusions: Letrozole alone or in combination with gonadotropin as a first-line treatment in PCOS may be reasonable since this approach may improve the success rate and minimize the overall costs and risks. Â